The Influence of Knowledge Management and Green Innovation on the Environmental Performance of MSMEs in Malang City: A Study of the Laundry Sector - Susilowati, Christin; Barinta, Dunga Dwi (Jurnal Manajemen Bisnis, 2024)
Improving business management by incorporating environmental considerations has become a critical aspect of ensuring business continuity. Environmental performance serves as an analytical tool for assessing the characteristics of business operations within a specific ecological context. Paying attention to environmental concerns, such as effective waste management practices and the development of environmentally friendly products, is pivotal for business success, particularly for small and medium-sized enterprises (MSMEs) engaged in chemical-intensive production processes. This study aims to investigate the role of knowledge management in fostering environmental performance and further explore the mediating effect of green innovation on this relationship. Utilizing a quantitative approach, this research collected data from 150 MSMEs in Malang City known to generate chemical waste, during the period of July to September, employing purposive sampling techniques. The findings of this study corroborate previous research indicating that robust knowledge management practices and proactive green innovation efforts significantly contribute to enhancing environmental performance. However, the analysis reveals that green innovation only partially mediates the relationship between knowledge management and environmental performance, suggesting avenues for further exploration in future research endeavors. Moreover, diversification in the selection of industries, expansion of research scopes, consideration of business scale variations, and exploration of additional relevant variables are deemed essential for advancing future research in this domain.